The Influence of Organizational Culture on Teachers' Work Ethic in Senior High School - Rakay Abdullah Sungkar; Riyuzen Praja Tuala; Sunarto Sunarto (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
Organizational culture is one of the important factors in shaping the professionalism, discipline, responsibility, and commitment of teachers in the educational environment. A positive organizational culture is able to create a work environment that supports cooperation, effective communication, and increases teachers' work motivation. This study aims to analyze the influence of organizational culture on the work ethic of teachers at SMA Negeri 9 Bandar Lampung. This study uses a quantitative approach with a type of correlational research involving 70 teachers as a research sample through a total sampling technique. Data collection was carried out through questionnaires, observations, and documentation, while data analysis used Pearson Product Moment correlation test and simple linear regression with the help of IBM SPSS Statistics 25. Research shows that organizational culture has a positive and significant influence on teachers' work ethic. A conducive organizational culture is able to increase discipline, cooperation, professionalism, and commitment of teachers in carrying out educational tasks. In addition, positive organizational values also help create a more harmonious and productive school environment. Strengthening organizational culture is very important in improving teachers' work ethic and the quality of education. The school is expected to be able to develop positive organizational values through effective communication, cooperation, leadership support, and professional development on an ongoing basis. The next study is suggested to examine other variables such as leadership style, job satisfaction, motivation, and work environment in order to gain a more comprehensive understanding of the factors that affect teachers' work ethic.